Antimicrobial and Anti-Virulence Activity of Capsaicin Against Erythromycin-Resistant, Cell-Invasive Group A Streptococci - Marini, Emanuela; Magi, Gloria; Mingoia, Marina; Pugnaloni, Armanda; Facinelli, Bruna (Frontiers in Microbiology, 2015)
Capsaicin (8-methyl-N-vanillyl-6-nonenamide) is the active component of Capsicum plants (chilli peppers), which are grown as food and for medicinal purposes since ancient times, and is responsible for the pungency of their fruit. Besides its multiple pharmacological and physiological properties (pain relief, cancer prevention, and beneficial cardiovascular, and gastrointestinal effects) capsaicin has recently attracted considerable attention because of its antimicrobial and anti-virulence activity. This is the first study of its in vitro antibacterial and anti-virulence activity against Streptococcus pyogenes [Group A streptococci (GAS)], a major human pathogen. The test strains were previously characterized, erythromycin-susceptible (n=5) and erythromycin-resistant (n=27), cell-invasive pharyngeal isolates. The MICs of capsaicin were 64-128 μg/mL (the most common MIC was 128 µg/mL). The action of capsaicin was bactericidal, as suggested by MBC values that were equal or close to the MICs, and by early detection of dead cells in the live/dead assay. No capsaicin-resistant mutants were obtained in single-step resistance selection studies. Interestingly, growth in presence of sublethal capsaicin concentrations induced an increase in biofilm production (p ≤ 0.05) and in the number of bacteria adhering to A549 monolayers, and a reduction in cell-invasiveness and haemolytic activity (both p ≤ 0.05). Cell invasiveness fell so dramatically that a highly invasive strain became non-invasive. The dose-response relationship, characterized by opposite effects of low and high capsaicin doses, suggests a hormetic response. The present study documents that capsaicin has promising bactericidal activity against erythromycin-resistant, cell-invasive pharyngeal GAS isolates. The fact that sublethal concentrations inhibited cell invasion and reduced haemolytic activity, two important virulence traits of GAS, is also interesting, considering that cell-invasive, erythromycin-resistant strains can evade β-lactams by virtue of intracellular location and macrolides by virtue of resistance, thus escaping antibiotic treatment. By inhibiting intracellular invasion and haemolytic activity, capsaicin could thus prevent both formation of a difficult to eradicate intracellular reservoir, and infection spread to deep tissues.